2021
DOI: 10.32457/ijmss.v8i2.1355
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical effects of carnosic acid on human hepatocellular carcinoma HepG2 cells

Abstract: Antecedentes / objetivo : La muerte celular autofágica y la apoptosis de células tumorales se ha convertido en uno de los principales objetivos en el tratamiento del cáncer, mientras que las líneas celulares tumorales se utilizan principalmente en estudios para proporcionar datos importantes para la evaluación de posibles sustancias anticancerígenas. En este estudio, nuestro objetivo fue evaluar los cambios morfológicos y bioquímicos, incluida la tasa de apoptosis y los niveles de alfa fetoproteína (AFP) a dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Recent studies have reported the cytotoxicity of rosemary extracts on breast cancer (70,77). Carnosic acid is cytotoxic to lung (78,79), gastric (80), and liver cancer cells (81). Carnosol and rosmanol are cytotoxic to liver cancer cells (81) and breast cancer cells (82), respectively.…”
Section: Rosemary and Other Cancersmentioning
confidence: 99%
“…Recent studies have reported the cytotoxicity of rosemary extracts on breast cancer (70,77). Carnosic acid is cytotoxic to lung (78,79), gastric (80), and liver cancer cells (81). Carnosol and rosmanol are cytotoxic to liver cancer cells (81) and breast cancer cells (82), respectively.…”
Section: Rosemary and Other Cancersmentioning
confidence: 99%